DELOS Nanovesicles-Based Hydrogels: An Advanced Formulation for Topical Use - Lídia Ballell-Hosa; Elisabet González-Mira; Hector Santana; Judit Morla-Folch; Marc Moreno-Masip; Yaima Martínez-Prieto; Albert Revuelta; Primiano Pio Di Mauro; Jaume Veciana; Santi Sala; Lidia Ferrer-Tasies; Nora Ventosa (MDPI AG, 2022)
Topical delivery has received great attention due to its localized drug delivery, its patient compliance, and its low risk for side effects. Recent developments have focused on studying new drug delivery systems as a strategy for addressing the challenges of current topical treatments. Here we describe the advances on an innovative drug delivery platform called DELOS nanovesicles for topical drug delivery. Previously, the production of DELOS nanovesicles demonstrated potentiality for the topical treatment of complex wounds, achieving well-tolerated liquid dispersions by this route. Here, research efforts have been focused on designing these nanocarriers with the best skin tolerability to be applied even to damaged skin, and on exploring the feasibility of adapting the colloidal dispersions to a more suitable dosage form for topical application. Accordingly, these drug delivery systems have been efficiently evolved to a hydrogel using MethocelTM K4M, presenting proper stability and rheological properties. Further, the integrity of these nanocarriers when being gellified has been confirmed by cryo-transmission electron microscopy and by Förster resonance energy transfer analysis with fluorescent-labeled DELOS nanovesicles, which is a crucial characterization not widely reported in the literature. Additionally, in vitro experiments have shown that recombinant human Epidermal Growth Factor (rhEGF) protein integrated into gellified DELOS nanovesicles exhibits an enhanced bioactivity compared to the liquid form. Therefore, these studies suggest that such a drug delivery system is maintained unaltered when hydrogellified, becoming the DELOS nanovesicles-based hydrogels, an advanced formulation for topical use.